A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus - Carvalho-Filho, Alfredo; de Oliveira, Joiciane; Soares, Camila; Araripe, Juliana (Zootaxa, 2019)
Centropomus irae sp. nov. (Centropomidae) is described from two localities in the state of Amapá, northern Brazil. The new species differs from all its congeners by the typically brown-colored lateral line, the relatively smaller mean interorbital width (4.1% of SL vs. 5.2–6.9%), mean snout length (8.9% of SL vs. 9.8–11.1%), mean diameter of the orbit (4.5% of SL vs. 5.4–7.3%), and mean mandible length (15.7% of SL vs.19.9–21.6%). The new species can also be distinguished from the similar Centropomus undecimalis by the number of scales around the caudal peduncle (18–23, usually 19–21, vs. 22–28, usually 24–27). With Centropomus irae sp. nov., seven species of the genus are now known to occur in the western Atlantic. The distribution of Centropomus in Brazilian waters is updated and a key to the species of this genus is presented. [Zoobank URL: urn:lsid:zoobank.org:act:3D497B38-48A5-4A6E-B377-6D57E82D4DE4[